Overexpression of E3 Ubiquitin Ligase Gene AdBiL Contributes to Resistance against Chilling Stress and Leaf Mold Disease in Tomato - Shuangchen Chen; Shuangchen Chen; Hongjiao Zhao; Mengmeng Wang; Jidi Li; Zhonghong Wang; Fenghua Wang; Airong Liu; Golam J. Ahammed (Frontiers in Plant Science, 2017)
Ubiquitination is a common regulatory mechanism, playing a critical role in diverse cellular and developmental processes in eukaryotes. However, a few reports on the functional correlation between E3 ubiquitin ligases and reactive oxygen species (ROS) or reactive nitrogen species (RNS) metabolism in response to stress are currently available in plants. In the present study, the E3 ubiquitin ligase gene AdBiL (Adi3 Binding E3 Ligase) was introduced into tomato line Ailsa Craig via Agrobacterium-mediated method. Transgenic lines were confirmed for integration into the tomato genome using PCR. Transcription of AdBiL in various transgenic lines was determined using real-time PCR. Evaluation of stress tolerance showed that T1 generation of transgenic tomato lines showed only mild symptoms of chilling injury as evident by higher biomass accumulation and chlorophyll content than those of non-transformed plants. Compared with wild-type plants, the contents of AsA, AsA/DHA, GSH and the activity of GaILDH, γ-GCS and GSNOR were increased, while H2O2, O2.−, MDA, NO, SNOs, and GSNO accumulations were significantly decreased in AdBiL overexpressing plants in response to chilling stress. Furthermore, transgenic tomato plants overexpressing AdBiL showed higher activities of enzymes such as G6PDH, 6PGDH, NADP-ICDH, and NADP-ME involved in pentose phosphate pathway (PPP). The transgenic tomato plants also exhibited an enhanced tolerance against the necrotrophic fungus Cladosporium fulvum. Tyrosine nitration protein was activated in the plants infected with leaf mold disease, while the inhibition could be recovered in AdBiL gene overexpressing lines. Taken together, our results revealed a possible physiological role of AdBiL in the activation of the key enzymes of AsA–GSH cycle, PPP and down-regulation of GSNO reductase, thereby reducing oxidative and nitrosative stress in plants. This study demonstrates an optimized transgenic strategy using AdBiL gene for crop improvement against biotic and abiotic stress factors.